2018
DOI: 10.1002/prca.201700164
|View full text |Cite
|
Sign up to set email alerts
|

Peptidome Analysis Reveals Novel Serum Biomarkers for Children with Autism Spectrum Disorder in China

Abstract: These findings reveal the exceptional disease etiology of ASD from a serum proteomic perspective, and the identified proteins might be potential biomarkers for ASD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Fewer proteomics studies on ASD have been published than those based on other disciplines, such as genomics or transcriptomics. Many of them rely on post-mortem brain tissues [ 50 , 51 , 52 ], serum [ 53 , 54 , 55 , 56 ], plasma [ 57 , 58 , 59 ], urine [ 63 ], saliva [ 60 , 61 , 62 ] direct samples or lymphoblastoid cell lines [ 64 ] ( Table 1 ).…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer proteomics studies on ASD have been published than those based on other disciplines, such as genomics or transcriptomics. Many of them rely on post-mortem brain tissues [ 50 , 51 , 52 ], serum [ 53 , 54 , 55 , 56 ], plasma [ 57 , 58 , 59 ], urine [ 63 ], saliva [ 60 , 61 , 62 ] direct samples or lymphoblastoid cell lines [ 64 ] ( Table 1 ).…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
“…In another study, apolipoproteins involved in cholesterol metabolism were found to be increased in an ASD cohort with respect to the control subjects [ 54 ]. In addition, two studies reported an alteration in proteins implicated in lipid metabolism, in the inflammation process and cell growth [ 55 , 56 ] ( Table 1 ).…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
“…These findings suggest that TAARs might play an important role in autism spectrum disorders (Huang et al 2016). Accordingly, the peptidome analysis of 68 Han Chinese children with autism and 80 healthy controls allowed the identification of 8 potential serum biomarker peaks, including TAAR6 (Yang et al 2018). A significantly different peak area of the TAAR6 fragment was also reported in 30 patients with vascular cognitive impairment, relative to 30 healthy controls (Xi et al 2009).…”
Section: Exome Sequencing and Changes In Taar Gene Expressionmentioning
confidence: 92%
“…Transcriptomics studies use cDNA microarrays and high-throughput RNA sequencing technology to obtain gene expression data, combining with gene co-expression network analysis to discover the molecular mechanisms related to ASD [15,16]. Proteomics studies have found that the clinical manifestations of ASD may be related to changes in proteins, such as mutations leading to changes in protein and amino acid sequences, and mutations in gene regulatory regions leading to changes in protein expression or abnormal modification of proteins [17,18]. In recent years, the acquisition of specific biomarkers through metabolomics research is effective for early ASD screening and diagnosis.…”
Section: Introductionmentioning
confidence: 99%